Cellular and humoral immune responses to viral antigens create barriers to lung-directed gene therapy with recombinant adenoviruses. - Yang, Y (1995)
Recombinant adenoviruses are an attractive vehicle for gene therapy to the lung in the treatment of cystic fibrosis (CF). First-generation viruses deleted of E1a and E1b transduce genes into airway epithelial cells in vivo; however, expression of the transgene is transient and associated with substantial inflammatory responses, and gene transfer is significantly reduced following a second administration of the virus. In this study, we have used mice deficient in immunological effector functions in combination with adoptive and passive transfer techniques to define antigen-specific cellular and humoral immune responses that underlie these important limitations. Our studies indicate that major histocompatibility complex class I-restricted CD8+ cytotoxic T lymphocytes are activated in response to newly synthesized antigens, leading to destruction of virus infected cells and loss of transgene expression. Major histocompatibility complex class II-associated presentation of exogenous viral antigens activates CD4+ T-helper (TH) cells of the TH1 subset and, to a lesser extent, of the TH2 subset. CD4+ cell-mediated responses are insufficient in the absence of cytotoxic T cells to completely eliminate transgene containing cells; however, they contribute to the formation of neutralizing antibodies in the airway which block subsequent adenovirus-mediated gene transfer. Definition of immunological barriers to gene therapy of cystic fibrosis should facilitate the design of rational strategies to overcome them.